Enhanced control of Bacillus subtilis endospores development by hyperbaric storage at variable/uncontrolled room temperature compared to refrigeration. (September 2018) - Pinto, Carlos A.; Santos, Mauro D.; Fidalgo, Liliana G.; Delgadillo, Ivonne; Saraiva, Jorge A.
Abstract: The effect of hyperbaric storage on Bacillus subtilis endospores, as a new food preservation methodology with potential to replace the conventional refrigeration processes, was assessed and compared to refrigeration. To do so, three different matrices (McIlvaine buffer, carrot juice and brain-heart infusion broth, BHI-broth) were inoculated with B. subtilis endospores and stored at 25, 50 and 100 MPa at variable/uncontrolled room temperature (18–23 °C), under refrigeration (4 °C), and room temperature at atmospheric pressure (0.1 MPa), up to 60 days. Two different quantification procedures were performed to assay both vegetative and endospores (unheated samples) and endospores (heated samples), to assess germination under pressure. The results showed that hyperbaric storage yielded pronounced endospore loads reductions in carrot juice and BHI-broth at 50 and 100 MPa, while in McIlvaine buffer, lower endospore loads reductions were observed. At 25 MPa, the endospores germinated and outgrew in carrot juice. Under refrigeration conditions, both carrot juice and BHI-broth underwent endospore germination and outgrowth after 60 and 9 days of storage, respectively, while in McIlvaine buffer there were no endospore outgrowth. These results suggest that hyperbaric storage at room temperature might not only be a feasible preservation procedure regarding endospores, but also that the food product (matrix characteristics) seems to influence the microbial inactivation that occurs during hyperbaric storage. Highlights: Hyperbaric storage/room temperature (HS/RT) avoided Bacillus subtilis spores growth. At 50/100 MPa, HS/RT reduced spore loads in McIlvaine buffer, carrot juice and BHI. Spores in carrot juice and BHI reached the quantification limit (2.00 log CFU/mL). Globally, HS/RT enhanced B. subtilis spores germination control versus RF. HS can extend pasteurized foods shelf-life by spore inactivation.